The Approach of Knowledge Transfer in Deriving Shafi‘ite Hukum - Wan Hassan, W.Z.; Alias, J.; Jamsari, E.A.; Abdullah, L.; Abdullah, S. (Mediterranean Center of Social and Educational Research, 2015)
The management and transfer of knowledge have been actively discussed lately, specifically in relation to managing information. However, it is not yet actively pursued from other angles, for example, relating to religion, especially Islam. This paper takes the perspective of the making of the rules, specifically by the Shafi‘ites, by seeing how knowledge transfer can be carried out in the process of hukum making. The knowledge transfer approach through the ‘replication’ and ‘adaptation’ methods will be emphasised and fully explained. This paper will also show that the process of establishing a rule in the Shafi‘i madhhab applied knowledge transfer via replication and adaptation. Using these two approach, the Shafi’ites seem to have successfully expanded their teachings globally. In fact, these applications were able to solve many problems of the Islamic community today.